2012
DOI: 10.1016/j.jvs.2012.06.105
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of a 3-week and 6-week vascular surgery simulation course on junior surgical residents' performance of an end-to-side anastomosis

Abstract: An open vascular simulation course consisting of three weekly 1-hour sessions increased the surgical skill of junior residents in performing a vascular end-to-side anastomosis to that of senior residents on a standardized assessment. A 6-week course provided no additional benefit. This study supports the use of an open vascular simulation course to teach vascular surgical skills to junior residents. A course consisting of three 1-hour sessions is an effective and efficient component of a simulation program for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…These "basic" skills should be included in future simulation based training programs. 16 Basic open vascular skills, including construction of a vascular anastomosis, ranked number one in the final list, which is in line with national surveys performed in Denmark and the United States. 13,17 Vascular anastomosis is a fundamental component of open vascular surgery and should be mastered by every vascular surgeon.…”
Section: Discussionsupporting
confidence: 72%
“…These "basic" skills should be included in future simulation based training programs. 16 Basic open vascular skills, including construction of a vascular anastomosis, ranked number one in the final list, which is in line with national surveys performed in Denmark and the United States. 13,17 Vascular anastomosis is a fundamental component of open vascular surgery and should be mastered by every vascular surgeon.…”
Section: Discussionsupporting
confidence: 72%
“…A workshop was organized since numerous studies have demonstrated the successful acquisition of vascular anastomosis skills using both low-fidelity and high-fidelity simulators. 21 , 22 The curriculum of the workshop dictates how effective a particular simulator will be in providing clinically relevant and useful skills. 20 It is known that distributed practice (short practice sessions with intervals between sessions) results in better acquisition and retention compared with massed practice (practicing a task continuously in one long session).…”
Section: Discussionmentioning
confidence: 99%
“…Robinson compared a 6-week workshop with a 3-week workshop and reported that a 6-week course provided no additional benefit. 21 In addition, in a busy residency program, participation in the laboratory should be mandatory. 25 With that in mind, our workshop was conducted over a 3-week period, with a 1-hour training session/week, as a mandatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…The following references [ 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ] are cited in Supplementary Tables.…”
Section: Supplementary Materialsmentioning
confidence: 99%